2010
DOI: 10.1111/j.1539-6975.2009.01335.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Interaction Between Insurance Choice and Medical Care Demand

Abstract: The gross price elasticity of demand for medical care is decomposed into two separate "observable" components: the medical care gross price elasticity of insurance choice and the cost-sharing elasticity of medical care. When consumers alter their choice of health-care plans, the price elasticity of medical care is no longer equivalent to the cost-sharing elasticity; using the latter as a proxy for the former may produce misleading results. We present conditions under which the medical care price elasticity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Two studies assessed the interaction between insurance and health services consumption as well as demand (26,33). Blomqvist and Leger in a study assessing the interaction between insurance and health services utilization, found out that in the context where the doctors were paid by capitation and patients who paid only part of the cost of their health services, the physician practice was significantly influenced by information asymmetry, patient cost sharing and fee-for-service payment method (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies assessed the interaction between insurance and health services consumption as well as demand (26,33). Blomqvist and Leger in a study assessing the interaction between insurance and health services utilization, found out that in the context where the doctors were paid by capitation and patients who paid only part of the cost of their health services, the physician practice was significantly influenced by information asymmetry, patient cost sharing and fee-for-service payment method (26).…”
Section: Resultsmentioning
confidence: 99%
“…Dusansky, in a study, assessed the effects of the interaction between insurance choice and medical service demand and reported that an increase in price for medical services led to a decrease in the request for medical services and also an increase in the request for more insurance coverage. However, the increase in insurance coverage increased the demand for medical services (33).…”
Section: Resultsmentioning
confidence: 99%
“…We can find numerous work devoted to managing risks in energy [5,6,7,8], in chemistry and pharmaceutical industry [9,10,11,12] aeronautic and space [13,14], automotive [15] and recently those related to the use of information technology [16,17]. Other fields are also concerned, such as finance and banking [18], insurance and health [19]. In France there is a long tradition of managing industrial risks using statistic methods, recently extended by Bayesian and some data mining [20,21]].…”
Section: Related Workmentioning
confidence: 99%
“…There exists also a rich U.S. literature on health plan choice that is not focused on irrational behavior (Dowd and Feldman, ; Cutler and Reber, ; Royalty and Solomon, ; Strombom,Buchmueller, and Feldstein, ; Atherly,Dowd,and Feldman, ; Buchmueller, ; Bundorf, ; Dusansky and Koç, ; Parente et al, ; Buchmueller et al, ). Excellent literature overviews are provided by Kolstad and Chernew () and Gaynor and Town ().…”
mentioning
confidence: 99%